PENGARUH LITERASI KEUANGAN, INKLUSI KEUANGAN, DAN INOVASI TERHADAP KINERJA UMKM - Nadziro, Rismanda Armenisa; Mustahidda, Rahmania (ITB AAS Indonesia Surakarta, 2024)
This study aims to determine the influence of financial literacy, financial inclusion, and innovation on the performance of MSMEs in Pedurungan District. The independent variables analyzed in this study are financial literacy, financial inclusion, and innovation. The dependent variable analyzed in this study is the performance of MSMEs. The sample used in this research is MSME players in the Pedurungan District area. Sampling using purposive sampling technique with the sovin formula obtained a sample of 90 respondents. The method for analyzing this research data uses validity tests, reliability test, normality tests, multicollinearity tests, heteroscedasticity tests, t tests, F tests, and coefficient of determination tests. The data analysis technique used is multiple linear regression analysis with the help of data processing software SPSS version 22. The results of this study indicate the financial literacy has a negative and significant effect on MSME performance, financial inclusion has a positive and significant on MSME performance, innovation has a positive and significant effect on MSME performance.